Cost-Effectiveness of Extended Electrocardiogram Monitoring for Atrial Fibrillation After Stroke: A Systematic Review. Issue 7 (July 2020) - Chew, Derek S.; Rennert-May, Elissa; Spackman, Eldon; Mark, Daniel B.; Exner, Derek V.
Abstract : Background and Purpose: Management of cryptogenic stroke involves the identification of modifiable risk factors, such as atrial fibrillation (AF). Extended rhythm monitoring increases AF detection rates but at an increased device cost compared with conventional Holter monitoring. The objective of the study was to identify and synthesize the existing literature on the cost-effectiveness of prolonged rhythm monitoring devices for AF detection in cryptogenic stroke. Methods: We conducted a systematic review of available economic evaluations of prolonged ECG monitoring for AF detection following cryptogenic stroke compared with standard care. Results: Of the 530 unique citations, 8 studies assessed the cost-utility of prolonged ECG monitoring compared with standard care following cryptogenic stroke. The prolonged ECG monitoring strategies included 7-day ambulatory monitoring, 30-day external loop recorders or intermittent ECG monitoring, and implantable loop recorders. The majority of cost-utility analyses reported incremental cost-effectiveness ratios below 50 000 per QALY gained; and two studies reported a cost-savings. Conclusions: There is limited economic literature on the cost-effectiveness of extended ECG monitoring devices for detection of atrial fibrillation in cryptogenic stroke. In patients with cryptogenic stroke, extended ECG monitoring for AF detection may be economically attractive when traditional willingness-to-pay thresholds are adopted. However, there was substantial variation in the reported ICERs. The direct comparison of cost-effectiveness across technologies is limited by heterogeneity in modeling assumptions. Abstract : Supplemental Digital Content is available in the text.